Meningkatkan Kemampuan Membaca Permulaan Melalui Media Video Pembelajaran Bahasa Indonesia Bagi Anak Disabilitas Intelektual Ringan - Parima, Nela; Irdamurni, Irdamurni (Universitas Negeri Padang, 2024)
This research was motivated by a preliminary study conducted at SLB Negeri 1 Muaro Sijunjung, which showed that students with mild intellectual disabilities, particularly in the third grade, were unable to read words and sentences clearly. The aim of the study is to improve the activity, motivation, and learning outcomes of students in Indonesian language lessons, especially in reading, through the use of video learning methods. This research is a Classroom Action Research (CAR) conducted in collaboration with third-grade teachers. The subjects of the research consisted of three third-grade students with mild intellectual disabilities, namely FA, HB, and AR. The results showed a significant improvement in early reading skills: Student FA improved from 25% (initial condition) to 30% (cycle I) and 75% (cycle II); student HB from 20% (initial condition) to 30% (cycle I) and 65% (cycle II); and student AR from 25% (initial condition) to 40% (cycle I) and 70% (cycle II). Based on the research results, it can be concluded that the video learning method is effective in improving the early reading skills of students with mild intellectual disabilities in the third grade at SLB Negeri 1 Muaro Sijunjung